Estado nutricional de los adultos mayores del Centro Gerontológico de la ciudad de Saraguro. - Albito Balcázar, Adriana Fernanda (2017)
In the last decades of the twentieth century there was an interest in learning about the role of nutrition in the elderly. It had double motivation, on one hand the progressive increase in this segment of the population. On the other hand, the ignorance until that time about what the nutritional needs were, as it were considered the same as young people. For that reason, a descriptive and transversal study was conducted in order to assess the state of nutrition of the elderly by applying the Mini Nutritrional Assessment (MNA) and biochemical indicators (albumin, prealbumin, transferrin, lymphocytes and cholesterol) in the Gerontology center in Saraguro city. The sample was composed of 100 adults older than 65 years old and others who got the inclusion criteria. From the 100 people evaluated 63 ones are women and 37 ones are men. The average age for women is 74 and for men is 73 years old. Applying the MNA, the 75% of people had a normal nutritional status, 25% of them were at risk of malnutrition and cases of malnutrition were not found. The average of albumin is 4.79 g. /dL, prealbumin 29.96 g / dL, transferrin 286.52 mg / dL, lymphocytes 28.89% and cholesterol 170.68 mg / dL. Concluding that most of elderly people are in good nutritional status. Keyword: Elderly, Nutrition, Nutritrional Assessment, albumin, prealbumin, transferrin, lymphocytes and cholesterol